2022
DOI: 10.1192/bjo.2022.58
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and well-being during the second wave of COVID-19: longitudinal analyses of the UK COVID-19 Mental Health and Wellbeing study (UK COVID-MH)

Abstract: Background Waves 1 to 3 (March 2020 to May 2020) of the UK COVID-19 Mental Health and Wellbeing study suggested an improvement in some indicators of mental health across the first 6 weeks of the UK lockdown; however, suicidal ideation increased. Aims To report the prevalence of mental health and well-being of adults in the UK from March/April 2020 to February 2021. Method Quota sampling was employed at wave 1 (March/April 2020), and online surveys were conducted at seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 24 publications
5
27
0
Order By: Relevance
“…Notwithstanding the adoption of this regional approach consisting of lighter restraining measures than the first lockdown, some longitudinal investigations showed a persistent impact of the emergency period on sleep (Conte et al, 2021; and mental health among the Italian population during the second contagion wave. These results were consistent with the international literature confirming long-lasting repercussions on sleep features (Basishvili et al, 2021;Liu et al, 2022;Trakada et al, 2022) and psychological measures (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) during the second COVID-19 wave, suggesting the urgency of large-scale interventions to preserve the general well-being. In the last days of 2020, the administration of the first COVID-19 vaccine to the adult population was authorised by the European and Italian medicines agencies.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Notwithstanding the adoption of this regional approach consisting of lighter restraining measures than the first lockdown, some longitudinal investigations showed a persistent impact of the emergency period on sleep (Conte et al, 2021; and mental health among the Italian population during the second contagion wave. These results were consistent with the international literature confirming long-lasting repercussions on sleep features (Basishvili et al, 2021;Liu et al, 2022;Trakada et al, 2022) and psychological measures (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) during the second COVID-19 wave, suggesting the urgency of large-scale interventions to preserve the general well-being. In the last days of 2020, the administration of the first COVID-19 vaccine to the adult population was authorised by the European and Italian medicines agencies.…”
Section: Introductionsupporting
confidence: 92%
“…Specifically, younger people (Amicucci et al, 2021;Daly et al, 2020;Jahrami et al, 2022;Rossi et al, 2020) and women (Daly et al, 2020;Rossi et al, 2020;Salfi et al, 2020;Salfi, Lauriola, et al, 2021) reported higher rates of sleep disturbances and psychological symptoms. These results were confirmed by Italian and European studies (Benke et al, 2022;Chodkiewicz et al, 2021;Rus Prelog et al, 2022;Wetherall et al, 2022) addressing the effect of the second wave of COVID-19. Similarly, the evening chronotype was associated with more evident changes in sleep patterns and increased sleep and mental health problems both during the lockdown (Bottary et al, 2022;Merikanto et al, 2022;Salfi, Lauriola, et al, 2021) and the second contagion wave .…”
Section: Introductionsupporting
confidence: 67%
“…Changes in daily life have also been accompanied by significant changes in mental health and wellbeing during and after the pandemic. Analysis from cross-sectional, cohort and longitudinal studies indicates that for many, mental wellbeing deteriorated during the pandemic [30][31][32][33][34][35]. Specifically, during periods of lockdown there were increases in feeling of boredom, isolation, anxiety and depression for many [30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis from cross-sectional, cohort and longitudinal studies indicates that for many, mental wellbeing deteriorated during the pandemic [30][31][32][33][34][35]. Specifically, during periods of lockdown there were increases in feeling of boredom, isolation, anxiety and depression for many [30][31][32][33][34][35]. There were also significant increases in worry, and to a lesser extent rumination, during periods of lockdown throughout the first year [36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation